Yolk hormones and sexual conflict over parental investment in the pied flycatcher - Laaksonen, Toni (Springer-Verlag, 2010)
Female birds might be able to manipulate the parental effort of their male partner through elevated transfer of hormones to the eggs, since these hormones affect many chick traits that males might use as cues for adjusting the level of their investment. We experimentally studied whether female pied flycatchers Ficedula hypoleuca could manipulate male investment via yolk androgens. There is much more variation in yolk androgen levels between females than within clutches, and in order to change the androgen levels of the eggs, we swapped whole clutches between nests. To estimate the androgen levels of the clutch, we measured the androgen content of a single egg per clutch. Females did not succeed in manipulating male effort using yolk androgens, since there was no relationship between the division of parental care within a pair and either original or foster egg androgen levels. One of these relationships should have occurred if females were manipulating males. The proportion of feeding visits by the male was higher when the male was old (55%) than when he was young (45%) and females laid eggs with higher androgen levels when mated with a young male. Young males did not exhibit any responses to yolk androgen levels either, which indicates that females cannot exploit their effort more than that of old males. We suggest that females may allocate yolk androgens to adjust the growth trajectories of the chicks to poor growing conditions when mated with young males that are poor providers or occupying a poor territory.